2013
DOI: 10.1039/c3cp44381g
|View full text |Cite
|
Sign up to set email alerts
|

Sieving di-branched from mono-branched and linear alkanes using ZIF-8: experimental proof and theoretical explanation

Abstract: We study the adsorption equilibrium isotherms and differential heats of adsorption of hexane isomers on the zeolitic imidazolate framework ZIF-8. The studies are carried out at 373 K using a manometric set-up combined with a micro-calorimeter. We see that the Langmuir model describes well the isotherms for all four isomers (n-hexane, 2-methylpentane, 2,2-dimethylbutane and 2,3-dimethylbutane). The linear and mono-branched isomers adsorb well, but 2,2-dimethylbutane is totally excluded. Plotting the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 64 publications
12
69
0
2
Order By: Relevance
“…This is about 3 Å larger than the selective size and more than twice the XRD-window size. Moreover, the work of Ferreira et al [19] suggests, that the selective size depends on temperature. At 373 K 2,2-dimethylbutane and 2,3-dimethylbutane could be separated effectively suggesting an selective aperture size of up to 6 Å.…”
Section: Propane and Propenementioning
confidence: 99%
See 1 more Smart Citation
“…This is about 3 Å larger than the selective size and more than twice the XRD-window size. Moreover, the work of Ferreira et al [19] suggests, that the selective size depends on temperature. At 373 K 2,2-dimethylbutane and 2,3-dimethylbutane could be separated effectively suggesting an selective aperture size of up to 6 Å.…”
Section: Propane and Propenementioning
confidence: 99%
“…In the following, just a few of them shall be mentioned. Thus, molecules with critical diameter substantially exceeding the XRD window size of ZIF-8 (3.4 Å) were found to be adsorbed [15][16][17][18][19][20]. This is attributed to the flexibility of the ZIF-8 structure.…”
Section: Introductionmentioning
confidence: 96%
“…Dubbeldam et al 21 reported a mixed sorption hierarchy while Herm et al, 22 by introducing intracrystalline diffusional resistances, stated a normal sorption hierarchy. Thereafter, Ferreira et al 23 studied the hexane isomers sorption under static conditions where only the dibranched isomer 22DMB was not adsorbed. Zhang et al 24 also studied the sorption of hexane isomers under static conditions and completely different results were obtained, being the dibranched isomer 23DMB most preferable adsorbed than its respective monobranched and linear isomers.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic diameter is a reflection of the smallest effective dimension of a given molecule (Figure 2 of Ref. ). This parameter is used for determining the number of molecules that cover the surface of the catalyst.…”
Section: Theorymentioning
confidence: 99%